1999
DOI: 10.1209/epl/i1999-00563-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved monitoring of the evolution of the breakdown of the quantum Hall effect: Direct observation of inter-Landau-level tunneling

Abstract: We have measured the evolution of breakdown of the quantum Hall effect along a macroscopic constriction on a GaAs/AlGaAs 2DEG heterostructure. From the evolution of the dissipative resistivity along the drift direction, we conclude that electrons are excited to the upper Landau level at a constant rate which exponentially depends on the Hall voltage. The results are explained on the basis of impurity mediated tunneling of electrons between the Landau levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…In the previous studies of Kaya et al, 6,7 the authors concluded that the relaxation and excitation of the electrons near the QHE breakdown are due to the inter-Landau-level transitions, which are triggered by Coulomb scattering at impurities. We can consider the case for the Hall bars and assume that these impurities are distributed homogeneously throughout the sample as shown in Fig.…”
Section: A a Simple Drift Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…In the previous studies of Kaya et al, 6,7 the authors concluded that the relaxation and excitation of the electrons near the QHE breakdown are due to the inter-Landau-level transitions, which are triggered by Coulomb scattering at impurities. We can consider the case for the Hall bars and assume that these impurities are distributed homogeneously throughout the sample as shown in Fig.…”
Section: A a Simple Drift Modelmentioning
confidence: 98%
“…9 The reverse experiments of the excitation of electrons from the QH state to the dissipative state also showed a clear correlation between the mobility ͑or the scattering density͒ and the spatial evolution of the QHE breakdown along a constriction in the current path. 7,10 With increasing density of scatters ͑decreasing mobility͒, the avalanchelike breakdown became steeper along the drift direction. However, it was not possible to estimate the corresponding excitation times exc in these experiments.…”
Section: ͒mentioning
confidence: 99%
“…Longitudinal resistivity makes a rather gradual transition into dissipative regime with the increased current. Critical currents at filling factors ν = ±2 between the probes (6-7), (7)(8) at B = 11 T , T = 1.4 K. Inset shows ρ15,76 vs jx for ν = −2 with the full range of currents. b) σxx versus 1/jx in semilog scale.…”
Section: A)mentioning
confidence: 99%
“…b) σxx versus 1/jx in semilog scale. Inset shows fittings at filling factors ν = ±2 between the probes (6-7), (7)(8) at B = 11 T , T = 1.4 K for the region jx = 1 − 2 A/m. Fig.…”
Section: A)mentioning
confidence: 99%
“…Under quantizing conditions, high resistance contacts contribute to thermal excitation of electrons to higher Landau levels by Joule heating, leading to high uncertainty in metrological measurements of R K . 9 For GaAs heterostructures with alloyed AuGeNi contacts, it has been shown that high contact resistance values in the ∼kΩ range translate into deviations of the measured quantum Hall resistance from R K /2 up to 1 part per million. 10 Conversely, deviations can be <1 part per billion, if the resistance of the voltage contacts is below 100 Ω.…”
mentioning
confidence: 99%